Analysis of Cultural Identity among Generation Z in the Gebyar Pelajar Lampung Community through Instagram - Nurhidayah, Indah; Waskito, Budhi; Verawati, Noning (Interaction Communication Studies Journal, 2025)
This study aims to analyze how Generation Z members of the Gebyar Pelajar Lampung (GPL) Community construct and represent their cultural identity through the social media platform Instagram. Using a descriptive qualitative approach, data were collected through in-depth interviews, Instagram content observation, and visual documentation. The study is guided by Cultural Identity Theory and Stuart Hall’s Representation Theory. The findings reveal that the cultural identity of GPL members is shaped through five key dimensions: (1) existence and self-actualization, (2) social and cultural representation, (3) social connection, (4) personal branding and digital aesthetics, and (5) motivations behind digital identity construction. The results indicate that Instagram is not merely a platform for visual communication, but a strategic space for youth to actively and creatively negotiate cultural identity. Social media serves as a crucial arena for Generation Z in building personal and collective identity in the midst of digital culture development.